Integração de sistemas de gestão normalizados: um panorama de empresas de engenharia consultiva - Franco, Marco Antonio Cortellazzi (2015)
The aim of this study was to evaluate the adoption of standard management systems ISO 9001, ISO 14001 and OHSAS 18001 and the integration of their management into a single system on the Brazilian consulting engineering companies. The research was conducted with the highest income organizations in the sector, in order to identify the reasons for the implementation, the difficulties encountered and the benefits obtained by its adoption. To achieve this goal, an exploratory survey was conducted in a non-random sample using as a data collection instrument a questionnaire available on the internet, achieving approximately a 27% rate of return. The majority of responses were considered reliable by the application of a Cronbach test and correlated by Pearson at 95% confidence level, which makes reliable the analysis of the results. The results obtained showed that there is no culture in most Brazilian consulting engineering firms to adopt standardized management system, and among firms that own more than a standard management system only 25% has integrated its management in a single system. For the implementation of an integrated management system the answers to the questionnaire indicated as the only reason for its adoption, the strategic decision of the company, the main difficulty has been low motivation of employees and the main benefits obtained were the simplification of documentation, improvement of the company culture and an appropriate structure for the inclusion of new systems.